LEGALITAS PEMBUATAN AKTA RISALAH RAPAT UMUM PEMEGANG SAHAM DAN BERITA ACARA RAPAT YANG DIBUAT BERDASARKAN PASAL 77 AYAT 1 UNDANG-UNDANG NOMOR 40 TAHUN 2007 - ANGGIE T.H. SIHOTANG (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Sunarmi3. T. Keizerina Devi A According to Article 77 paragraph 1 of the Law No. 40/2007, RUPS (Shareholders’ General Meeting) which is held by means of electronic media can be conducted using teleconference and videoconference; however, UUPT (the Law on Limited Liability Companies) does not clarify the mechanism of the implementation. It is then very risky considering its mechanism is very essential as it determines the validity of the minutes of RUPS and any authentic deed resulted from the RUPS. The research problems are how the making of a Notarial deed for the RUPS held via electronic media is, what obstructs a Notary in implementing Article 77 paragraph 1 of the Law No. 40/2007 and how to prove the validity of the minutes of RUPS held via electronic media by the NotaryKeywords: Shareholders’ General Meeting, Limited Liability Company, General Meeting of Shareholders via Electronic Media